KOMUNIKASI PERSUASIF ORANG TUA DENGAN ANAK DALAM MEMBENTUK PERILAKU TAAT BERIBADAH DI DESA JATI KESUMA - Wulandari, Ai Wanda; Abidin, Syahrul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The phenomenon that occurs in the Jatikesuma Village community provides the background for this research, where parents use persuasive communication activities in the form of persuasion or invitations to their children, but not all parents apply it. This fact encourages the author to propose the forms of persuasive communication used by parents on their children, the obstacles faced by parents in their children, and the results achieved by parents on their children. The author used a qualitative research method by conducting field research and qualitative description, collecting qualitative data, and analyzing the data afterwards. The author collected data using observation, interviews, and documentation techniques. The results of this study are expected to provide an overview of the forms of persuasive communication used by parents on their children in the Jatikesuma Village community. The forms of child behavior in worship in Jatikesuma Village were found to be different in this study. This study identifies the forms of persuasive communication used by parents to their children in the form of persuasion or invitations, namely forcing the child, monitoring, complying with the child's wishes or providing rewards, and giving praise. This study also identifies obstacles faced by parents with their children, namely the lack of willingness from the child themselves, the child only performs worship when given a reward, the child spends too much time playing with their phone, and parents who do not care. The results achieved in this study include the increasing diligence of children in worship, the emergence of trust from parents towards their children, and the increasing willingness of children to read the Quran. The recommendations from this study include urging the village chief and religious figures to encourage the community to teach children to read the Quran and to perform prayers in congregation, urging parents to provide understanding and influence children to get used to and willing to perform worship from an early age, and urging children to perform worship and make the Quran a guide in a better life.